Hubungan Pengetahuan dan Sikap dengan Kepatuhan Konsumsi Obat pada Pasien Tuberkulosis di Puskesmas Pekauman Banjarmasin - Irvan Maulana; Fahrurazi Fahrurazi; Eddy Rahman (HB PRESS, 2020)
The disease of tuberculosis is a contagious disease and is increasing every year. The number of cases of tuberculosis in Indonesia in 2016 was 298,128 cases, while in South Kalimantan Province there were 5,147 cases. Tuberculosis (TB) is a chronic infectious disease that can be cured when taking medication regularly. Compliance of tuberculosis patients to take medication may be influenced by the knowledge and attitude of the patient. The purpose of this research is to know the correlation between knowledge and attitude with the compliance of drug consumption in tuberculosis patients in Pekauman Public Health Center Banjarmasin working area in 2018. The design of this study used analytical survey with cross sectional approach. The population is all TB patients in Pekauman Public Health Center Banjarmasin working area from February to June 2018, amounting to 56 people. The sample meets the criteria of 54 people with purposive sampling technique. Data analysis through chi-square test using 95% confidence level. TB patients in Pekauman Public Health Center Banjarmasin working area mostly have good knowledge about tuberculosis amounted to 39 people (72,2%), have positive attitude amounted to 48 people (88,9%), obedient in taking medicine of tuberculosis amounted to 48 people (88 , 9%). There is correlation between knowledge and attitude with compliance of drug consumption in tuberculosis patient in Pekakesmas Banjarmasin working area (p value = 0,000,031). For Pekauman Public Health Center Banjarmasin can improve health education for example by holding group meeting and special routine counseling to TB patient and family, and distributing leaflets / leaflets about TB drug consumption compliance.